2016
DOI: 10.1128/genomea.01747-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Whole-Genome Sequence of Trichoderma gamsii T6085, a Promising Biocontrol Agent of Fusarium Head Blight on Wheat

Abstract: Trichoderma gamsii T6085 is a promising beneficial isolate whose effects consist of growth inhibition of the main agents causing Fusarium head blight, reduction of mycotoxin accumulation, competition for wheat debris, and reduction of the disease in both the lab and the field. Here, we present the first genome assembly of a T. gamsii isolate, providing a useful platform for the scientific community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Besides, Trichoderma represents one of the most important expression systems that is widely used to produce industrial enzymes on large scale (Singh et al 2015 ). Up to now, the genome sequences of 13 Trichoderma strains have been completed (Halliwell and Griffin 1973 ; Martinez et al 2008 ; Kubicek et al 2011 ; Studholme et al 2013 ; Xie et al 2014 ; Baroncelli et al 2015 , 2016 ; Shikunne et al 2015 ; Yang et al 2015 ; Lee et al 2017 ), and the number keeps increasing. Sequence analysis of the genomes of T. viride , T. reesei , T. harzianum and T. gamsii indicated that Trichoderma harbors a great variety of lipase genes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Trichoderma represents one of the most important expression systems that is widely used to produce industrial enzymes on large scale (Singh et al 2015 ). Up to now, the genome sequences of 13 Trichoderma strains have been completed (Halliwell and Griffin 1973 ; Martinez et al 2008 ; Kubicek et al 2011 ; Studholme et al 2013 ; Xie et al 2014 ; Baroncelli et al 2015 , 2016 ; Shikunne et al 2015 ; Yang et al 2015 ; Lee et al 2017 ), and the number keeps increasing. Sequence analysis of the genomes of T. viride , T. reesei , T. harzianum and T. gamsii indicated that Trichoderma harbors a great variety of lipase genes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the release of the first complete Trichoderma genome sequence in 2008 belonging to the industrially important cellulase producer T. reesei (Martinez et al, 2008 ) and its subsequent comparative analysis with the genomes of the biocontrol species T. virens and T. atroviride (Kubicek et al, 2011 ; Schmoll et al, 2016 ), the number of full genome sequences publicly available in databases for Trichoderma strains is growing rapidly (Baroncelli et al, 2015 , 2016 ; Kuo et al, 2015 ; Shi-Kunne et al, 2015 ; Compant et al, 2017 ), which opens the way for using comparative genome analysis to identify specific endogenous markers. An example is the study of Mahfooz et al ( 2016 ), who performed a comparative in silico analysis of SSR sequences in the genomes of T. reesei and three biocontrol species of the genus, and developed 6-6 primer pairs for the amplification of polymorphic markers from T. atroviride and T. harzianum .…”
Section: “Omics” Approaches In the Service Of Trichoderma mentioning
confidence: 99%
“…The genome sequence of the mycotoxigenic F. graminearum ITEM 124 provides a novel source for comparative genomics studies and also represents a useful platform to study fungal-fungal interactions, such as the mycoparasitic relationship established with the beneficial isolate T. gamsii T6085, whose genome is also available ( 14 ).…”
Section: Genome Announcementmentioning
confidence: 99%